Thiol‐epoxy polymerization via an AB monomer: Synthetic access to high molecular weight poly(β‐hydroxythio‐ether)s. Issue 14 (25th April 2014) - Binder, Selmar; Gadwal, Ikhlas; Bielmann, Andreas; Khan, Anzar
ABSTRACT A synthetic route is developed for the preparation of an AB‐type of monomer carrying an epoxy and a thiol group. Base‐catalyzed thiol‐epoxy polymerization of this monomer gave rise to poly(β‐hydroxythio‐ether)s. A systematic variation in the reaction conditions suggested that tetrabutyl ammonium fluoride, lithium hydroxide, and 1, 8‐diazabicycloundecene (DBU) were good polymerization catalysts. Triethylamine, in contrast, required higher temperatures and excess amounts to yield polymers. THF and water could be used as polymerization mediums. However, the best results were obtained in bulk conditions. This required the use of a mechanical stirrer due to the high viscosity of the polymerization mixture. The polymers obtained from the AB monomer route exhibited significantly higher molecular weights (Mw = 47, 700, Mn = 23, 200 g/mol) than the materials prepared from an AA/BB type of the monomer system (Mw = 10, 000, Mn = 5400 g/mol). The prepared reactive polymers could be transformed into a fluorescent or a cationic structure through postpolymerization modification of the reactive hydroxyl sites present along the polymer backbone. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2040–2046